2008
DOI: 10.1364/oe.16.017196
|View full text |Cite
|
Sign up to set email alerts
|

Multipolar analysis of second-harmonic radiation from gold nanoparticles

Abstract: We present a multipolar tensor analysis of second-harmonic radiation from arrays of noncentrosymmetric L-shaped gold nanoparticles. Our approach is based on the fundamental differences in the radiative properties of electric dipoles and higher multipoles, which give rise to differences in the nonlinear response tensors for the reflected and transmitted second-harmonic signals. The results are analyzed by dividing the tensors into symmetric (dipolar) and antisymmetric (higher multipolar) parts between the two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 46 publications
1
50
0
Order By: Relevance
“…Secondharmonic generation has also been observed experimentally from ordered arrays of split-ring resonators, 50,51 as well as from a variety of single nanoparticles [52][53][54][55][56] and nanoparticle arrays with varying geometries. [57][58][59][60][61][62][63][64][65][66][67][68][69] On the theoretical side, Zeng et al readapted the free-electron theory of secondharmonic generation to arbitrary shaped metal nanoparticles. 70 Scalora et al have considered a dynamic description based on the hydrodynamic model and taken into account bound electron contributions to the second-and third-harmonic generation in the ultrashort pulse regime.…”
Section: Introductionmentioning
confidence: 99%
“…Secondharmonic generation has also been observed experimentally from ordered arrays of split-ring resonators, 50,51 as well as from a variety of single nanoparticles [52][53][54][55][56] and nanoparticle arrays with varying geometries. [57][58][59][60][61][62][63][64][65][66][67][68][69] On the theoretical side, Zeng et al readapted the free-electron theory of secondharmonic generation to arbitrary shaped metal nanoparticles. 70 Scalora et al have considered a dynamic description based on the hydrodynamic model and taken into account bound electron contributions to the second-and third-harmonic generation in the ultrashort pulse regime.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, SHG were experimentally observed from different geometric configurations such as sharp metal tips [28,32], periodic nanostructured metal films [29], imperfect spheres [31,35], split-ring resonators [34,40] and their complementary counterparts [42], metallodielectric multilayer photonic-bandgap structures [41], T-shaped [40] and L-shaped NPs [38,43], noncentrosymmetric T-shaped nanodimers [39,46] and "fishnet" structures [44].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the capability of mapping chiral local field enhancements is lost below the resolution limit of SHG microscopy; where, recently, it has been reported that, in ~300 nm large gold nanodimers at λ = 1060 nm, structural defects play an important role [43]. Structural defects, such as bumps, pits and other small-scale structural deviations [44], are well known sources of SHG enhancement [45,46] and it has been proposed that they contribute through effective higher order multipoles [47,48]. However, between 2.4 µm and 300 nm there is a wide range that remains unexplored.…”
Section: Introductionmentioning
confidence: 99%